Are they in or out? The elusive interaction between Qtracker®800 vascular labels and brain endothelial cells. (November 2015) - Radu, Beatrice Mihaela; Radu, Mihai; Tognoli, Cristina; Benati, Donatella; Merigo, Flavia; Assfalg, Michael; Solani, Erika; Stranieri, Chiara; Ceccon, Alberto; Fratta Pasini, Anna Maria; Cominacini, Luciano; Bramanti, Placido; et al.
Aim: Qtracker ® 800 Vascular labels (Qtracker ® 800) are promising biomedical tools for high-resolution vasculature imaging; their effects on mouse and human endothelia, however, are still unknown.Materials & methods: Qtracker ® 800 were injected in Balb/c mice, and brain endothelium uptake was investigated by transmission electron microscopy 3-h post injection. We then investigated, in vitro, the effects of Qtracker ® 800 exposure on mouse and human endothelial cells by calcium imaging.Results: Transmission electron microscopy images showed nanoparticle accumulation in mouse brain endothelia. A subset of mouse and human endothelial cells generated intracellular calcium transients in response to Qtracker ® 800.Conclusion: Qtracker ® 800 nanoparticles elicit endothelial functional responses, which prompts biomedical safety evaluations and may bias the interpretation of experimental studies involving vascular imaging.